EXQ: development and validation of a multiple-item scale for assessing customer experience quality - Klaus, Philipp (Cranfield University, 2010)
Positioned in the deliberations related to service marketing, the conceptualisation of service quality, current service quality measurements, and the importance of the evolving construct of customer experience, this thesis develops and validates a measurement for customer experience quality (EXQ) in the context of repeat purchases of mortgage buyers in the United Kingdom. The thesis explores the relationship between the customer experience quality and the important marketing outcomes of customer satisfaction, repeat purchasing behaviour, loyalty and word-of- mouth intentions. The methodology follows Churchill’s (1979) scale development paradigm approach to scale development and is also informed by the more recent publication of Walsh and Beatty (2007). This involves creating the EXQ scale from the following sequence of research activities: (a) employing a review of the literature on service marketing, service quality, service quality measurements, and customer experience research; (b) generating an initial item pool from qualitative research; (c) purifying and validating the EXQ scale through exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). The EXQ scale explains 63 per cent of all variances in customer satisfaction, more than 86 per cent of loyalty, and more than 94 per cent of word-of-mouth intentions. This is evidence of the high explanatory power of the EXQ scale for important marketing outcomes. This thesis represents both the first empirically derived conceptualisation of customer experience and the first validated measure of customer experience quality. It reports the findings collected from three independent samples of repeat mortgage buyers from a United Kingdom bank.